Determinants of hypertensive crisis among hypertensive patients at adult emergency departments of public hospitals in eastern Ethiopia, 2023: A case-control study - Fenta Wondimneh; Melaku Getachew; Tilahun Teshager; Henok Legesse; Ayichew Alemu; Indeshaw Ketema; Dejene Tesfaye; Yalew Mossie; Natan Muluberhan; Fentahun Meseret (PLoS ONE, 2025)
Background Hypertensive crisis is a life-threatening condition requiring urgent medical intervention. Identifying key determinants is essential for effective prevention and management. This study aimed to assess factors associated with hypertensive crisis among patients attending selected public hospitals in eastern Ethiopia. Methods A hospital-based unmatched case-control study was conducted among 357 participants (119 cases and 238 controls). Cases were hypertensive crisis patients, while controls were hypertensive patients without crisis in adult emergency departments of public hospitals in eastern Ethiopia from April 10th to September 10th, 2023. Data were collected using structured questionnaires and medical record reviews. Multivariable logistic regression was used to identify independent determinants of hypertensive crisis, with results presented as Adjusted Odds Ratios (AORs) and 95% Confidence Intervals (CIs). Results The mean age of participants was 54.7 ± 14.4 years for cases and 48.14 ± 15.51 years for controls. More than half of the cases (54.8%) and one-third of the controls (32.6%) were female. Multivariable analysis identified female sex (AOR = 2.91, 95% CI: 1.67–5.07), unemployment (AOR = 2.28, 95% CI: 1.20–4.33), diabetes mellitus (AOR = 3.33, 95% CI: 1.59–7.01), previous history of hypertension (AOR = 2.25, 95% CI: 1.21–4.19), drinking alcohol (AOR = 3.01, 95% CI: 1.45–6.24), and poor knowledge of hypertension (AOR = 1.86, 95% CI: 1.07–3.22) as significant determinants of hypertensive crisis (p < 0.05). Conclusion Female sex, unemployment, diabetes mellitus, history of hypertension, drinking alcohol, and poor hypertension knowledge were independent predictors of hypertensive crisis. However, the case-control design’s intrinsic limitations make it difficult to establish a temporal relationship between risk factors and outcomes. Strengthening hypertension education, promoting lifestyle modifications, and enhancing healthcare access may help mitigate the risk of hypertensive crisis.